Host-Reaction Following Silicone Tube Implantation For Lower Limb Lymphoedema Mimicking Implant Infection - Silva, Eduardo (2023)
Introduction: Silicone tube implantation in lymphoedema reduces symptoms by improving fluid drainage. Although there are descriptions of implant host reaction that can be misdiagnosed as graft infections these are scarce. Report: A 34 year old female with lymphoedema of the lower limb, underwent silicone tube implantation. Ten months after surgery, the patient presented with fever and dermatolymphangioadenitis of the limb. Ultrasound suggested an abscess surrounding the tubes. Clinical improvement was achieved after a 6-day cycle of meropenem. She was discharged under oral cefuroxime and clindamycin for one week. After 1 month, CT-angiography was performed showing only residual inflammation surrounding the tubes, the patient was asymptomatic and limb diameter was normal. Conclusion: Sudden onset and improvement of the patient’s condition after a short cycle of antibiotics without the need of tube removal supports a host-like reaction rather than an actual infection. Doctors should be aware of such complications avoiding unnecessary procedures.